Effect of the Protein Level to the Growth Rate of Three-breed Chickens - Voravit Siripholvat; Suchart Sangunphan (Agriculture and Natural Resources, 1992)
Two hundred and eighty-eight three-breed crossbred chickens from the native males cross with Changhai-Rhode females were used. The chickens were allocated and fed with 3 groups of commercial feed. The first group was fed with 22.48% protein of the broiler starter ration during day-old-6 week (wk), with 22.48% protein of the broiler starter and 21.45% protein of the grower ration in the same proportion during 7-9 wk. with 21.45% protein of the grower ration during 10-12 wk. The second group was fed with 21.45% protein of the broiler grower ration during day-old-6 wk. with 21.45% protein of the grower and 19.06% protein of the finisher ration in the same proportion during 7-9 wk. and 10-12 wk., respectively. The third group was fed with 19.06% protein of the broiler finisher ration during that 3 periods. The average body weight gain of the first, the second and the third group during day-old-6 wk. were 562.83, 497.11 and 385.07 grams (gm), during 7-9 wk. were 439.99, 424.52 and 403.99 gm. during 10-12 wk. were 427.38, 432.83 and 435.99 gm., respectively. The body weight gain data were statistically analyzed and found that it was highly significant only the period of day-old-6 wk. of age. The average feed consumption of the first, the second and the third during day-old-6 wk. of age were 1,043.37, 1,037.28 and 968.33 gm., during 7-9 wk. were 1,080.82, 1,082.42 and 1,025.68 gm., and during 10-12 wk. were 1,297.21, 1,360.11 and 1,304.77 gm., respectively. The feed conversion ratio of the first, the second and the third during day-old-6 wk. were 1.85, 2.09 and 2.52, during 7-9 wk. were 2.46, 2.55 and 2.54 and during 10-12 wk. were 3.04, 3.14 and 2.99 respectively. In consideration with weight gain per unit of feed cost, the highest weight gain per feed cost during day-old-6 wk. was the chickens fed with the first group of feed. But during 7-9 wk. and 10-12 wk. of age they were the chickens fed with third group.